Industrial precipitation of yttrium chloride and zirconyl chloride: effect of pH on ceramic properties for yttria partially stabilised zirconia - Carter, Geoffrey; Hart, Robert; Rowles, M.; Ogden, Mark; Buckley, Craig (Elsevier Science, 2009)
Two 3 mol% partially stabilised zirconia (P-SZ) samples suitable for the SOFC market were manufactured from solutions through to ceramics using a method similar to a known industrial process. The only difference in preparation of the two 3 mol% P-SZ samples was the pH of precipitation which was set at pH 3 or 12. Particle size measurements by dynamic light scattering were used to characterise the precipitate and the filtration rates were investigated. Five point N2-BET was used to investigate the specific surface area before and after calcination with the response to temperature tracked. Similarly TGA/DTA investigation was used to determine the calcination point during all of these tests and it was found that both powders behaved similarly. XRD-Rietveld analysis incorporating in situ and ex situ calcination revealed that the pH 3 sample had more monoclinic phase present after calcination and sintering as a ceramic. Ceramic testing incorporating hardness (Vickers), toughness (K1C), MOR, density and grain sizing was carried out, all determined that the material produced at pH 12was superior for SOFC applications than the pH 3 sample. Further investigation using TEM-EDS revealed that the processing of the pH 3 powder had allowed a lower concentration of the yttrium which was incorporated at approximately 2 mol% instead of the required 3. ICP-OES of the after filter liquor indicated that high concentrations of yttrium (797 ppm) were found in the solution with the wash solution having 149ppm yttrium. In contrast the pH 12 samples had 7ppm in both the after filter liquor andwash indicating that the yttrium is bound within the matrix more completely at the higher pH.